O arquiteto como incorporador?: uma discussão sobre a atuação convencional e outras possibilidades - Guilherme Nunes de Vasconcelos (2015)
This work arises with a bet on the entrepreneurial role of the architect as a possibility for the development of enterprises more interesting from architectural and urban viewpoints, disentangled from strictly financial interests of conventional developers. However, the simulation of the process of building production through a design course, in which the architects undertake via real estate development, it was noticed that by introducing economic and financial criteria to the design, the students tends to guide their decisions in a similar manner to that used by conventional developers, that is, by evaluating the profitability expected for the investment. This trend is also seen in the case study with three projects built by developer-architects of Belo Horizonte, which while well intentioned, reproduces the conventional production logic. From the user perspective, there´s no improvement over projects usually produced by conventional developers. The points raised leads to questioning the bet on entrepreneurship as an alternative, being necessary to include in the discussion the problem that gives rise to this uncritical reproduction of the capitalist mode of procution. In this context, the process of educating an architect and the development of their tools, requirement program and technical drawing, are presented and discussed, showing its practical limits and their alignment with the existing mode of production. From there, the work seeks solutions that transform the practice of the architect, aiming not just methodological changes, but the change of the economic logic, which must be based primarily on spaces use value, as suggested by the enjoyment economy proposed by Henry Lefebvre, enabling the creation of more democratic and open to user participation spaces. At the end, we present guidelines for a working process with these characteristics, that can be implemented immediately, with significant benefits to the user and with potential to put pressure on conventional developers.